Evaluating Drivers’ Response to Road Hazard: A Simulation Study - Navid Javanbakht; Babak Mirbaha (Advances in Civil Engineering)
The presence of unexpected conditions on the road increases the risk of collisions for drivers. To effectively manage these risks, drivers must first accurately perceive hazards and then respond appropriately. The behavior of drivers and their responses to potential road hazards are investigated in this study. It is possible that one motorist may opt to gradually reduce the velocity of their vehicle, while another individual in the same situation might opt for forceful braking at the moment of initial awareness. This indicates the divergence reactions of drivers to identical hazards. This study introduces the hazards response scale (HRS) as a metric to assess the differences in hazard response among participants and its effect on safe driving by undertaking a driving simulation study. The results reveal that a lower HRS index correlates with a higher level of driving safety. By evaluating the relationship between demographic variables and HRS, it was found that increasing age and driving experience are associated with lower HRS scores, thus enhancing driving safety. Notably, women exhibit lower HRS values than men, suggesting that they tend to drive more safely.